Albert Schweitzer: Out of My Life and Thought : An Autobiography - Zagorac, Ivana (Array, 2011)
The work is a review of the book by Albert Schweitzer: Out of My Life and Thought : An Autobiography ; The John Hopkins University Press, Baltimore, 2009.